The evaluation of gastroesophagel reflüx incidence in children with various symtoms by cintigraphy - Ahmet YARAMIŞ,; Fuat GÜRKAN,; Kenan HASPOLAT,; Bünyamin DİKİCİ,; Orhan DERMAN,; Murat SÖKER,; Süleyman YILMAZ, (Turkish Journal of Gastroenterology, 2019)
-